Hypogonadism in chronic obstructive pulmonary disease (COPD) – risk factors - Novkovic, Ljiljana; Lazic, Zorica; Petrovic, Marina; Cupurdija, Vojislav; Vujanac, Katarina; Cekerevac, Ivan (Vojnosanitetski pregled, 2021)
Abstract Bacground/Aim. Chronic obstructive pulmonary disease (COPD) is the leading cause of morbidity and mortality in pulmonary pathology. However, apart from its own pulmonary manifestations, this disease is also characterized by systemic effects, including hypogonadism which is described especially in the group of men with COPD. The aim of this study was to evaluate risk factors for hypogonadism in men with COPD. Methods. The study included 96 male patients with COPD in stable phase of the disease. All patients were checked for concentration of free testosterone in serum, markers of systemic inflammation, tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and C reactive protein (CRP), pulmonary function test, gas exchange parameters, a 6-minute walk test (6MWT), nutritional status and condition of skeletal muscle (midthigh muscle cross-sectional area – MTCSA using computed tomography). Results. Decreased value of free testosterone was found in 37.5% of the patients. In the group with hypogonadism (free testosterone < 4.5 pg/mL), we found significantly increased serum concentration of TNF-α (5.88 ± 3.21 vs. 3.16 ± 2.53 pg/mL; p < 0.05), significantly lower MTSCA (68.2 ± 18.72 vs. 91.1 ± 21.4 cm2; p < 0.05) and the 6MWT (268.33 ± 32.35 vs. 334.25 ± 43.25 m; p < 0.05). Lung function, gas exchange markers and body mass index (BMI) were similar in both groups. The multivariate regression analysis singled out serum value of TNF-α as an independent predictor of serum concentrations of free testosterone (B = -0.157; 95% confidence interval: -0.262–0.053). Conclusion. In our analysis we found that TNF-α as a marker of systemic inflammation is an independent predictor of the presence of hypogonadism in the patients with COPD. Our results indicate that hypogonadism predisposes to skeletal muscle wasting and exercise intolerance in male COPD patients.